9t-1=17

Simple and best practice solution for 9t-1=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t-1=17 equation:


Simplifying
9t + -1 = 17

Reorder the terms:
-1 + 9t = 17

Solving
-1 + 9t = 17

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 9t = 17 + 1

Combine like terms: -1 + 1 = 0
0 + 9t = 17 + 1
9t = 17 + 1

Combine like terms: 17 + 1 = 18
9t = 18

Divide each side by '9'.
t = 2

Simplifying
t = 2

See similar equations:

| 16=2x-1-x | | 4(g+5)=5(g-5) | | 3(2x-9)-3=3(x-4)+9 | | (2i+2)(4i-5)=0 | | 0.3+0.5x=2.3+x | | 144=3x+47+7x-13 | | 10=6+lnx | | -3(2x)= | | -560+(-40)=-600 | | -5n-4=-94 | | -5y+15=6 | | -3(5p+4)-2(4-11p)=3(9+2p) | | -5+15=6 | | 6x^2+11a+2=4 | | X=-120+59 | | 18a^2-10a+27a-15=0 | | -2a+3-a=0 | | 9=3a | | 4-2x-3=17 | | 3x-6y-7x+3y= | | 2z-9=21 | | 9(y+9)= | | -d=-2d+7 | | 4+2x+3=17 | | C+28=c+65 | | ((30)180)+((36)180)+((((8)9)6)36)+((((8)5)6)36)+((((8)7)7)36)+(18(7))+8500= | | 19+4(6c-1)= | | 4+2x-3=17 | | 8x-9=6x+29 | | (6i+5)-(-10i-5)=0 | | 4(3x-3)-2=4(x-4)+42 | | 3y-6y+2=8y+6-5 |

Equations solver categories